PENGARUH TEKNIK BEHAVIOR CONTRACT TERHADAP DISIPLIN BELAJAR SISWA KELAS VIII SMP N 6 TARAKAN TAHUN PELAJARAN 2018/2019 - Amin Reswastiyo; Siti Rahmi (Jurnal Bimbingan dan Konseling Borneo, 2019)
This research aims to know the influence of engineering behavior contract against a disciplined learning grade VIII SMP Negeri 6 Lesson 2018/2019 Year of Tarakan. This research uses research design pre-experimental with form one group pretest-posttest. Population of 212 students, people withdrawal sempel by using purposive sampling of as many as 7 people grade VIII. The instruments of this research using a scale discipline studied with likertscale, there is a valid item 29 of the 40 items. Data analysis techniques using descriptive statistics and analysis of inferensial using wilcoxon test with the help of 22.0 SPSS for windows. Based on the results of the study before and after administering treatment, obtained results calculation test hypotheses with decision-making based on the probability obtained the value of asymp sig = 0.018 α = 0.05 then Ho is rejected. Then it can be inferred that the engineering behavior contract effect on the discipline of studying grade VIII SMP Negeri 6 Lesson 2018/2019 Year of Tarakan.  Keywords : behavior contract, disciplined learning, students